Analisis Kualitas Audit Syariah di Indonesia - Disfa Lidian Handayani; Choiriyah; Choirunnisak, Choirunnisak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses what are the indicators for measuring Sharia audit quality? What factors influence the quality of Sharia audits? This research is a type of library research which focuses on managing qualitative data with data analysis methods using descriptive-analytical methods. The results of this research are. There are 6 indicators for measuring audit quality, namely: (a) Misstatement Detection, (b) conformity to applicable general standards SOP. (c), Compliance with SOPs, (d) Process Quality (accuracy of audit findings, skepticism). (e) Quality of results (value of recommendation, clarity of report, benefits of audit). (f). Quality of follow-up to audit results. There are 4 factors that influence audit quality, namely: (a) competency, (b) time pressure, (c) work experience. (d) Ethics.